A SEMIOTICS ANALYSIS OF THE STICKERS’ EXPRESSIONS USED BY THE MEMBERS OF GROUP OF FIB BERSEMI KEMBALI IN LINE MESSENGER - TITISARI, DIAH (Jurnal Ilmiah Mahasiswa FIB, 2013)
Communication is a process of giving understanding to the hearer aboutwhat is meant by the speaker. As stated by Raymond S. Ross (1983) as cited inMulyana (2004, p.62) that communication is a process in choosing and sendingsymbols by the speaker to be understood by the hearer. One of media which ismostly  used to communicate is messenger. LINE messenger is one of the newinstant messaging applications used by society. In this study, the writer conductsthe semiotics analysis of the stickers’ expressions in LINE messenger. There arethree problems to be solved in this study, namely: (1) Which stickers’ expressionsof each character are frequently used by the members of group FIB BersemiKembali in LINE messenger, (2) What are the meanings of the stickers’expressions of each character which are frequently used by the members of groupFIB Bersemi Kembali in LINE messenger, and (3) To what extent those stickers’expressions of each character support the users’ messages. This study uses descriptive qualitative approach since the writer analysesthe visual picture as signifiers and the concept of meanings as signified as thedata. The analysis is included to document analysis because the data are takenfrom the stickers’ expressions in LINE messenger.  The analysis aims to answer the problems of the study. In the analysis, thedata were analyzed based on Peirce’s triadic model of sign which consists ofrepresentamen, interpretant, and object. Moreover to support interpreting thestickers, the writer also uses the theory of colors based on theory of colors by Gonet al (2005), Morton (2000), and Smith (2013). This study reveals that Moon’s expressions which are frequently used bythe member of group FIB Bersemi Kembali are the expression number 4, 12, 15,and 2. James’ expressions which are frequently used are number 24, 18, 44, and17. Brown’s expressions which are frequently used are number 16, 13, 22, and 17.Meanwhile, Cony’s expressions which are frequently used are number 36, 16, 21,and 14. There are some elements to build the interpretation toward the stickers’expressions. They are colors, lines, dots, gestures and accessories of eachexpression. The stickers’ expressions also support the user’s messages since thewriter finds that the stickers’ expressions are multi-interpreted and can be used insome contexts of conversations. The writer suggests  the next researchers to broaden the semiotics scope inanalysing the stickers’ expressions by using other theories. Moreover, the writeralso suggests the next researchers to analyze other stickers’ expressions in LINEmessenger aside from those top four stickers’ expressions of each character whichhave been analyzed by the writer. Keywords: semiotics, Peirce’s triadic model of sign, LINE messenger, sticker,stickers’ expressions